2020
DOI: 10.1503/cmaj.190999
|View full text |Cite|
|
Sign up to set email alerts
|

Five-year risk of admission to long-term care home and death for older adults given a new diagnosis of dementia: a population-based retrospective cohort study

Abstract: BACKGROUND: After diagnosis of a health condition, information about sur vival and potential transition from com munity into institutional care can be helpful for patients and care providers. We sought to describe the association between a new diagnosis of dementia and risk of admission to a longterm care home and death at 5 years. METHODS:We conducted a population based retrospective cohort study using linked health administrative databases. We identified individuals aged 65 years or older, living in the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Studies in Norway [30], Korea [31], and Canada [32] estimated the median survival time between 3.3 and 9.1 years, and a German study [33] estimated the mean survival time to be 3.1 years; however, these studies did not report trends in mortality over time. A recent study from Ontario reported that the 5-year mortality for individuals diagnosed with dementia in community settings between 2010 and 2012 was 55.1%, and that 48.4% transitioned to LTC within 5 years [6]. These results are comparable to our study, which ob-served that 42.7% of PLWD transition to LTC, 49.6% die within 5 years, and the median time to LTC admission and death was not realized.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Studies in Norway [30], Korea [31], and Canada [32] estimated the median survival time between 3.3 and 9.1 years, and a German study [33] estimated the mean survival time to be 3.1 years; however, these studies did not report trends in mortality over time. A recent study from Ontario reported that the 5-year mortality for individuals diagnosed with dementia in community settings between 2010 and 2012 was 55.1%, and that 48.4% transitioned to LTC within 5 years [6]. These results are comparable to our study, which ob-served that 42.7% of PLWD transition to LTC, 49.6% die within 5 years, and the median time to LTC admission and death was not realized.…”
Section: Discussionsupporting
confidence: 84%
“…Restricting Dement Geriatr Cogn Disord 2020;49:286-294 DOI: 10.1159/000508687 our analysis to the community-dwelling population helps policymakers tailor community-based services. The validated dementia ascertainment algorithm used in this study has been implemented in other research related to dementia [6,12,35]. Lastly, by studying multiple objectives we provide a comprehensive picture of communitydwelling PLWD, where results may be generalized to other developed countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review and meta-analysis of people with dementia by van de Vorst et al [ 33 ] coronary artery disease and chronic heart failure were associated with mortality. A recent Canadian study of community dwelling people at the time of dementia diagnosis also reported increased risk of death with chronic heart failure, but did not report on other cardiac diseases [ 8 ]. However, A Dutch study restricted to people with AD found no association of history of cardiovascular disease (including stroke) and mortality, [ 7 ] but the lack of association may be due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings have often been inconsistent. For example, male gender [ 4 8 ], lower education level [ 9 ], and older age at diagnosis [ 4 8 , 10 12 ] have been associated with higher risk of death in people with dementia, while these associations have not been observed in other studies [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%